Pan American Day of Rheumatology: Patient-Centered Research - Global Rheumatology by PANLAR (Global Rheumatology, 2022)
May 31 marks Pan American Rheumatology Day. Global Conversations, a podcast, and videocast where we will talk about patient-centered research.